Design and Effect of Escape Vent in a Trap on the Catch of Blue Swimming Crab (Portunus Pelagicus): A Preliminary Study - Rahman, Muhammad Arif; Iranawati, Feni; Sambah, Abu Bakar (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Blue Swimming Crab (Portunus pelagicus, BSC) is one of the Indonesian important fisheries commodities often captured by traps. Under Decree No. 56/2016, the Ministry of Marine Affairs and Fisheries managed the BSC, with the standard size of BSC is >10cm of Carapace Width (CW) or >60 g of Weight (W), and non-berried or carried eggs for female. This study aims to determine BSC's crawling pattern toward the trap, design an escape vent on the trap, and assess catch of BSC using vented trap and non-vented trap. The video footage was used to examine crawling pattern of 30 BSCs on the laboratory. The study also includes field experiment by deploying twenty traps (10 vented traps and 10 non-vented traps) on the sea. The study obtained two crawling patterns of BSC, crawling forward and sideways with the most BSC crawled sideways. Design of escape vent was 4.6 cm length x 2.6 cm height. The BSCs captured in the vented traps have >10cm of CW, while 14% of BSCs in the non-vented traps have <10 cm of CW. The use of escape vent did not affect the catch (weight) of BSC in the trap.